DETERMINAN MINAT MEMILIH KARIR MENJADI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK - Fikri Rizki Utama; Umarudin Kurniawan (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
The number of public accountants in Indonesia experienced a sharp decline in the 2017-2018 period. Even though there are 203 Public Accounting Firms (KAP) in Indonesia registered with the OJK, the data shows that students' opportunities for a career as a public accountant can be even greater. This study aims to obtain empirical evidence on the influence of motivation, professional training, income, and work environment on interest in choosing a career to become an AP or non-AP. The method used in this study is the survey method and the sampling used is the convenience sampling method with the criteria of Islamic accounting students from 2017 to 2021. This study showed that the variables of motivation, professional training, and income showed influence on the interest in choosing a career to be AP and non-AP. While the work environment variable does not affect the interest in choosing a career to become AP or non-AP.